Developments in Electronic Nursing Logbooks in Health Service Areas: Literatur Review - Tsania Ayu Zaharany; Rr. Tutik Sri Hariyati (Poltekkes Kemenkes Semarang, 2020)
Background: Efforts to reduce the impact of the logbook vacancy and facilitate nurses in documentation in the industry 4.0 era have been developed with electronic logbooks (E-logbooks) used for more accurate documentation and assessing performance based on the achievement of individual utility activities. . The electronic logbook (E-logbook) of nurses is designed to be a documentation that records the achievement of activities, nurses' skills, and updates all activities, such as Continuous Professional Development (CPD), and is used in assessing employee behavior for 1 (one) year .Purpose: Make a summary and analysis of articles related to the nurse's Electronic logbook (E-logbook).Methods: Literature review is done by making a summary and analysis of the article. The method of searching articles in the literature review uses several electronic databases, namely Google Scholar, PubMed, JHA Science Direct, CINAHL, and ProQuest with the keywords electronic logbook nursing. The impact of the Elcetronic logbook on individual performance assessments that reflect staff competencies and performance and is carried out objectively and transparently so that the potential also increases the motivation of clinical staff which can lead to increased productivity and quality of health service.Results: Nurse e-Logbook has an important role, namely as evidence of documentation of the implementation of activities and clinical supervision.Conclusion: In Indonesia, only a small portion of health services, which already uses an electronic logbook program.